The role of integrins in pulmonary fibrosis - D. Sheppard (European Respiratory Review, 2008)
Integrins are a large family of transmembrane glycoprotein receptors initially identified as mediators of cell adhesion and tissue integrity. However, it is now known that the primary function of integrins in mammals is to act as signalling proteins. Signals from integrins are known to play critical roles in virtually every aspect of the behaviour of epithelial cells and in the development of certain pathological conditions, including pulmonary fibrosis. In this respect, the interaction between transforming growth factor-β, which is known to be pivotal in the development of pulmonary fibrosis, and the integrin alphaVβ6 is of particular interest. Integrin alphaVβ6 is responsible for the activation of constitutively expressed latent transforming growth factor-β by a mechanism that allows for temporal and spatial activity control. There is increasing evidence that this mechanism plays a critical role in the pathological activity of transforming growth factor-β. Although other activation mechanisms have been identified, studies suggest that alphaVβ6-mediated activation of transforming growth factor-β is necessary for the development of fibrosis in lung-disease models. The data from such studies imply that integrins may be attractive targets for intervention in pulmonary fibrotic diseases, such as idiopathic pulmonary fibrosis.